‘Gotong Royong’ by UMP students to clean up Batu Hitam beach - Amir Haziq, Ibrahim (2019)
A total of 40 volunteers comprising Universiti Malaysia Pahang (UMP) students from the Siswa Brigade Section 19G took part in a programme called, ‘Stay Clean With UMP’ which involved cleaning up the popular beach of Batu Hitam in Beserah here on March 30, 2019.